Double-base nano oil-water fracturing temporary plugging agent
By adopting the technical means of double-base nano oil-water fracturing temporary plugging agent in the fracturing temporary plugging agent, and utilizing the cross-linked network structure and the hydrophobic properties of the composite reinforcement materials, the existing fracturing temporary plugging agents have solved the problems of low compressive strength and easy Problems of shedding and poor stability under high salinity are achieved, achieving a higher blocking rate and longer stability.
Patent Information
- Application Number
- CN202411849122.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing fracturing temporary plugging agent has low compressive strength and is prone to fall off, and has poor long-term stability under high salinity. Nanoparticles are prone to migrating and precipitating in the temporary plugging agent, affecting the sealing effect.
Using double-base nano-oil-water fracturing temporary plugging agent, starch, acrylic acid, acrylamide, styrene and composite reinforcement materials are stirred evenly in the solvent, initiator and cross-linking agent are added, and the reaction is carried out under specific temperature and time conditions. , forming a cross-linked network structure. The composite reinforcement material is composed of shell powder loaded with nano-zirconium dioxide, modified montmorillonite and stearic acid. It forms a hydrophobic structure through chemical bonds and physical entanglement to improve compressive strength and stability.
It improves the compressive strength and plugging rate of the fracturing temporary plugging agent, prolongs the stability under high salinity, avoids the migration and precipitation of nanoparticles, enhances the salt resistance and long-term stability of the temporary plugging agent, and improves The recovery rate of recovery factor and core permeability is determined.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas development, in particular to a double-base nano oil-water fracturing temporary plugging agent. Background Art
[0002] Oil and natural gas are currently the most widely used non-renewable energy sources. With the large-scale exploitation of oil and gas energy, the exploitation of low-permeability oil and gas resources is particularly important. The reserves of low-permeability oil and gas resources account for 30% of the total oil reserves, and low-permeability unexploited reservoirs account for more than 50% of all unexploited reservoirs. Therefore, the development of low-permeability oil and gas fields is of great significance to the development of my country's petroleum industry. By adding temporary plugging materials to the fracturing fluid (temporary plugging balls to plug holes, temporary plugging agents with fracturing fluid to plug the ends of fractures), the original liquid inflow direction is changed, prompting other perforation clusters or formations to open new fractures, and finally forming multiple new branch fractures, so as to achieve the purpose of fine transformation of the reservoir.
[0003] Temporary plugging and diverting fracturing technology is an important and efficient development technology for oil and gas reservoir resources. It uses temporary plugging agents to effectively temporarily plug the cracks, effectively preventing the fracturing fluid from entering the old cracks, and then diverting fracturing to produce one or more new cracks, thereby expanding the cracks and finally forming a new crack network. After the fracturing construction is completed, the temporary plugging agent can be dissolved in the bottom layer, and with the production and discharge, the formation permeability is restored, the contact between the wellbore and the oil and gas reservoir is maximized, and the recovery rate is improved; however, the existing fracturing temporary plugging agents have low compressive strength and are easy to fall off, resulting in low sealing efficiency. By adding inorganic materials to the temporary plugging agents, the compressive strength of the temporary plugging agents can be effectively improved, but the inorganic materials have poor dispersibility in the temporary plugging agents and are easy to migrate and precipitate, affecting the sealing effect of the temporary plugging agents. In addition, the water absorption rate of the fracturing temporary plugging agents is fast, and the long-term stability under high salinity is poor, which affects the effective temporary plugging of the fracturing temporary plugging agents. Summary of the invention
[0004] The invention provides a dual-base nano oil-water fracturing temporary plugging agent, which solves the problems of low compressive strength, easy shedding, poor long-term stability under high salinity and easy migration and precipitation of nanoparticles in the temporary plugging agent.
[0005] The technical solution of the present invention: A double-base nano oil-water fracturing temporary plugging agent, comprising the following raw materials in parts by weight: 10-12 parts of starch, 10-15 parts of acrylic acid, 20-22 parts of acrylamide, 10-12 parts of styrene, 5-6 parts of composite reinforcing material, 0.05-0.15 parts of initiator, 0.5-0.6 parts of cross-linking agent, and 60-80 parts of solvent; A method for preparing a double-base nano oil-water fracturing temporary plugging agent comprises the following preparation steps: Add starch, acrylic acid, acrylamide, styrene and composite reinforcing material to the solvent, stir evenly, add initiator and cross-linking agent, stir at 45-55°C for 25-35 minutes, stir and react at 70-75°C for 2-4 hours, cool to room temperature, wash and precipitate solids, and dry the solids to obtain an oil-water fracturing temporary plugging agent.
[0006] The composite reinforcement material is prepared by mixing shell powder loaded with nano zirconium dioxide, modified montmorillonite and stearic acid; The shell powder loaded with nano zirconium dioxide is prepared by subjecting shell powder to an acidification treatment, and then mixing it with zirconium oxychloride octahydrate, and then subjecting it to a hydrothermal reaction; The modified montmorillonite is prepared by reacting 1-bromohexadecane with 2-(dimethylamino)ethyl methacrylate and then mixing with montmorillonite.
[0007] Furthermore, the starch is corn starch.
[0008] Furthermore, the cross-linking agent is N,N'-methylenebisacrylamide.
[0009] Furthermore, the initiator is dibenzoyl peroxide.
[0010] Furthermore, the solvent is ethyl acetate.
[0011] Furthermore, the composite reinforced material is specifically prepared by the following steps: A1. Add 1-bromohexadecane and 2-(dimethylamino)ethyl methacrylate to ethanol, stir evenly, heat to 45-55°C, stir and react for 20-22h, evaporate by rotary evaporation, add acetone for recrystallization, take out, wash and obtain a monomer; A2. The montmorillonite was added to deionized water, stirred evenly, the monomer was added, and stirring was continued for 10-12 hours. After washing with ethanol, the precipitate was filtered and dried to obtain the modified montmorillonite; A3. The shell powder was immersed in a nitric acid solution having a mass fraction of 5-6%, immersed for 40-50min, removed, washed, dried, placed in a grinder, and sieved through a 500-600 mesh screen to obtain acidified shell powder; A4. Add zirconium oxychloride octahydrate to deionized water, stir evenly, add 25-30% by mass of ammonia water, glycine and potassium chloride, stir evenly, add acidified shell powder, stir evenly, place in a reactor, perform hydrothermal reaction at 175-185°C for 20-24h, cool to room temperature, filter, wash and dry to obtain shell powder loaded with nano zirconium dioxide; A5. The shell powder loaded with nano zirconium dioxide is added to N, N-dimethylformamide, stirred evenly, stearic acid is added, stirred until the stearic acid is dissolved, stirred at 70-80 ° C for 20-22h, filtered, washed, and dried to obtain a composite; A6. Add the composite and modified montmorillonite to ethanol, stir evenly, stir at 50-60°C for 1-2h, heat to 80-85°C, stir until ethanol evaporates, take out the solid, wash and dry the solid to obtain a composite reinforced material.
[0012] Furthermore, in the above reaction process A1, the bromine atom in 1-bromohexadecane can react with the tertiary amino group in 2-(dimethylamino)ethyl methacrylate, so that 1-bromohexadecane is grafted onto 2-(dimethylamino)ethyl methacrylate to synthesize a monomer.
[0013] Furthermore, during the above-mentioned A2 reaction process, the cationic functional groups contained in the monomer can undergo an exchange reaction with the cations between the sodium-montmorillonite layers, so that the monomer is intercalated into the sodium-montmorillonite layers. After vigorous stirring, exfoliated sodium-montmorillonite is formed, and the monomer is adsorbed on the surface of the exfoliated sodium-montmorillonite to form modified montmorillonite.
[0014] Furthermore, during the above-mentioned A3 reaction process, nitric acid can react with calcium carbonate in shell powder to generate soluble nitrates, and can remove organic matter and impurities in shell powder, expose the original pore structure of shell powder, increase the specific surface area and pore structure of shell powder, and increase the contact area between shell powder and cracks.
[0015] Furthermore, in the above-mentioned A4 reaction process, the porous structure of the acidified shell powder has excellent adsorption performance, and can adsorb the zirconium ions in the zirconium oxychloride octahydrate into the pores of the shell powder. Ammonia water, as an alkaline precipitant, can react with the zirconium ions in the zirconium oxychloride octahydrate to generate a zirconium hydroxide precipitate, and a zirconium hydroxide precipitate is formed on the surface and in the pores of the acidified shell powder. A hydrothermal reaction is carried out at 180°C for 24 hours to decompose the formed zirconium hydroxide precipitate, and the additives glycine and potassium chloride can adjust the crystal phase of zirconium dioxide, so as to form 100-200nm nano zirconium dioxide on the surface and in the pores of the acidified shell powder.
[0016] Furthermore, during the above-mentioned A5 reaction, in the organic solvent N,N-dimethylformamide, the carboxyl group contained in stearic acid can combine with the hydroxyl group on the surface of the shell powder loaded with nano-zirconium dioxide through chemical bonds, so that stearic acid is grafted on the surface of the shell powder loaded with nano-zirconium dioxide to form a complex.
[0017] Furthermore, during the A6 reaction, the long alkyl chains on the surface of the modified montmorillonite can be entangled with the stearic acid chains on the surface of the composite to form hydrophobic channels, so that the modified montmorillonite is deposited on the surface of the composite to form a composite reinforcement material.
[0018] Furthermore, in step A1, the volume ratio of 1-bromohexadecane, 2-(dimethylamino)ethyl methacrylate and ethanol is (18-22):(10-12):(80-120).
[0019] Furthermore, in step A2, the ratio of the amount of montmorillonite, deionized water and monomer is (4-6) g: (45-55) mL: (0.3-0.6) g.
[0020] Furthermore, in step A3, the ratio of the shell powder to the nitric acid solution is (8-12) g: (45-55) mL.
[0021] Furthermore, in step A4, the usage ratio of zirconium oxychloride octahydrate, deionized water, ammonia water, glycine, potassium chloride and acidified shell powder is (3.9-4.3) g:(18-22) mL:(8-12) mL:(0.5-1.5) g:(1-3) g:(5-6) g.
[0022] Furthermore, in step A5, the amount ratio of the shell powder loaded with nano zirconium dioxide, N,N-dimethylformamide and stearic acid is (5-7) g: (45-55) mL: (2-3) g.
[0023] Furthermore, in step A6, the ratio of the composite, modified montmorillonite and ethanol is (5-6 g):(1-2) g:(45-55) mL.
[0024] Furthermore, the montmorillonite is sodium montmorillonite, with a particle size of 2-3 μm and a content of 84.5-86.5%.
[0025] Furthermore, the shell powder has a particle size of 1-2 mm and a calcium carbonate content of 95%.
[0026] The present invention has the following beneficial effects: (1) In the technical scheme of the present invention, 1-bromohexadecane reacts with 2-(dimethylamino)ethyl methacrylate, and the resulting monomer is mixed with sodium montmorillonite. The cationic functional groups contained in the monomer can exchange with the cations between the sodium montmorillonite layers, so that the monomer is intercalated into the sodium montmorillonite layers. After vigorous stirring, an exfoliated sodium montmorillonite is formed. The long hydrophobic chains of the monomers are entangled with each other, forming a hydrophobic network structure on the surface of the exfoliated sodium montmorillonite, thereby reducing the water absorption rate of the temporary plugging agent for oil-water fracturing. , promote the uniform distribution of oil-water fracturing temporary plugging agents in the cracks, increase the plugging rate, and alleviate the water absorption and swelling rate of the oil-water fracturing temporary plugging agents, avoid the water absorption and swelling rate of the fracturing temporary plugging agents being too fast, resulting in the agglomeration and failure of the fracturing temporary plugging agents, affecting the plugging efficiency, so that the oil-water fracturing temporary plugging agents have enough time to reach the bottom layer, plug the cracks, and improve the recovery rate. In addition, the exfoliated sodium-montmorillonite also has good salt resistance and long-term stability, which improves the long-term stability of the oil-water fracturing temporary plugging agents under high salinity.
[0027] (2) In the technical scheme of the present invention, the shell powder is treated with acid to increase the specific surface area and pore structure of the shell powder, increase the contact area between the shell powder and the cracks, facilitate entry into the micropores of the cracks, and improve the density of the temporary plugging layer; nano zirconium dioxide is formed on the surface and in the pores of the acidified shell powder, which can refine the pore size of the acidified shell powder, reduce the water absorption rate of the acidified shell powder, and avoid the shell powder being added to the oil-water fracturing temporary plugging agent. Due to the rapid water absorption rate of shell powder, the long-term stability of the oil-water fracturing temporary plugging agent under high salinity is poor, which affects the effective temporary plugging of the fracturing temporary plugging agent, and the addition of nano zirconium dioxide can effectively improve the compressive strength of the fracturing temporary plugging agent; in addition, when the oil-water fracturing temporary plugging agent absorbs water and swells to form a colloid, the shell powder slowly absorbs water, so that the nano zirconium dioxide in the shell powder is released, which can block the coarse pore surface of the colloid and improve the compressive strength and sealing effect of the colloid.
[0028] (3) In the technical solution of the present invention, the carboxyl group contained in stearic acid can be combined with the hydroxyl group on the surface of the shell powder loaded with nano zirconium dioxide through chemical bonds, so that the stearic acid is grafted on the surface of the shell powder loaded with nano zirconium dioxide to form a complex, which converts the shell powder loaded with nano zirconium dioxide from a hydrophilic structure to a hydrophobic structure, thereby avoiding the agglomeration of the shell powder loaded with nano zirconium dioxide.
[0029] (4) In the technical solution of the present invention, the composite material is mixed with modified montmorillonite. The long alkyl chains on the surface of the modified montmorillonite can be entangled with the stearic acid chains on the surface of the composite material, so that the modified montmorillonite is deposited on the surface of the composite material and entangled with each other to form hydrophobic channels, making it difficult for the water adsorbed into the oil-water fracturing temporary plugging agent to overflow, thereby providing a large amount of water absorption and retention space for the oil-water fracturing temporary plugging agent, thereby preventing the oil-water fracturing temporary plugging agent from becoming fragile and easy to break due to dehydration when the oil-water fracturing temporary plugging agent absorbs water and swells to form colloidal particles, thereby affecting the plugging effect.
[0030] (5) In the technical scheme of the present invention, starch, acrylic acid, acrylamide and styrene are used as raw materials. Under the action of initiator and cross-linking agent, a cross-linked network oil-water fracturing temporary plugging agent is formed. The agent has amphiphilicity and high pressure bearing capacity. It can seal the end of the fracture with the fracturing fluid, change the inflow direction of the original liquid, and promote other perforation clusters or formations to open new fractures. The formed oil-water fracturing temporary plugging agent also has good degradability. After degradation, the core permeability recovery rate is high, and it has a good temporary plugging and diversion effect. The monomers contained on the surface of the formed composite reinforcement material and the double bonds carried can also be cross-linked and copolymerized with acrylic acid, acrylamide and styrene, so that the composite reinforcement material acts in the oil-water fracturing temporary plugging agent system, increasing the cross-linking density of the oil-water fracturing temporary plugging agent and improving the compressive strength. In addition, the composite reinforcement material and the oil-water fracturing temporary plugging agent are combined by covalent bonds, which improves the bonding force between the composite reinforcement material and the matrix of the oil-water fracturing temporary plugging agent. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.
[0033] Among them, starch is corn starch, food grade, from Beijing Xiangyu Biotechnology Co., Ltd.
[0034] The cross-linking agent is N,N'-methylenebisacrylamide; The initiator is dibenzoyl peroxide.
[0035] The solvent was ethyl acetate.
[0036] The montmorillonite is sodium montmorillonite with a particle size of 2.5 μm and a content of 85.5%, from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0037] The particle size of shell powder is 1.5mm, and the calcium carbonate content is 95%, Qingdao Wanyuan Biotechnology Co., Ltd. Example
[0038] A double-base nano oil-water fracturing temporary plugging agent, comprising the following raw materials in parts by weight: 10 parts of starch, 10 parts of acrylic acid, 20 parts of acrylamide, 10 parts of styrene, 5 parts of composite reinforcing material, 0.05 parts of dibenzoyl peroxide, 0.5 parts of N,N'-methylenebisacrylamide, and 60 parts of ethyl acetate; A method for preparing a double-base nano oil-water fracturing temporary plugging agent comprises the following preparation steps: Starch, acrylic acid, acrylamide, styrene and composite reinforcing materials are added to the solvent and stirred evenly. Dibenzoyl peroxide and N,N'-methylenebisacrylamide are added and stirred at 45°C for 25 minutes until the starch is gelatinized. The mixture is stirred and reacted at 70°C for 2 hours. The mixture is cooled to room temperature and washed with deionized water until a solid is precipitated. After the solid is dried, an oil-water fracturing temporary plugging agent is obtained.
[0039] The composite reinforced material is specifically prepared by the following steps: A1. Add 18 mL of 1-bromohexadecane and 10 mL of 2-(dimethylamino)ethyl methacrylate to 80 mL of ethanol, stir evenly, heat to 45°C, stir and react for 20 hours, then evaporate by rotary evaporation, add acetone for recrystallization, take out, and wash with acetone three times to obtain a monomer; A2. 4 g of sodium montmorillonite was added to 45 mL of deionized water, stirred evenly, heated to 35 ° C, and stirred until no aggregates were observed, 0.3 g of monomer was added, stirred for 10 h, and the resulting product was washed with ethanol to remove water and excess monomers. The precipitate was filtered and dried in an oven at 50 ° C for 20 min to obtain modified montmorillonite; A3. 8 g of shell powder was immersed in 45 mL of 5% nitric acid solution for 40 min, then taken out, washed with deionized water until the washing solution was neutral, dried in an oven at 70°C for 10 min, crushed in a grinder, and passed through a 500-mesh sieve to obtain acidified shell powder; A4. Add 3.9 g of zirconium oxychloride octahydrate to 18 mL of deionized water, stir evenly, add 8 mL of 25% ammonia water, 0.5 g of glycine and 1 g of potassium chloride, stir evenly, add 5 g of acidified shell powder, stir at 85°C for 10 min, place in a reactor, perform hydrothermal reaction at 175°C for 20 h, cool to room temperature, filter, wash with deionized water until no chloride ions are detected in the supernatant with silver nitrate solution, and dry in an oven at 80°C for 3 h to obtain shell powder loaded with nano zirconium dioxide; A5. 5 g of shell powder loaded with nano zirconium dioxide was added to 45 mL of N, N-dimethylformamide, stirred evenly, 2 g of stearic acid was added, stirred until the stearic acid was dissolved, stirred at 70 ° C for 20 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 20 min to obtain a composite; A6. Add 5 g of the composite and 1 g of modified montmorillonite to 45 mL of ethanol, stir evenly, stir at 50 ° C for 1 h, heat to 80 ° C, stir until the ethanol evaporates, take out the solid, wash the solid with deionized water 3 times, and dry it in an oven at 80 ° C for 10 min to obtain a composite reinforced material. Example
[0040] A double-base nano oil-water fracturing temporary plugging agent, comprising the following raw materials by weight: 11 parts of starch, 13 parts of acrylic acid, 21 parts of acrylamide, 11 parts of styrene, 5.5 parts of composite reinforcing material, 0.1 parts of dibenzoyl peroxide, 0.55 parts of N,N'-methylenebisacrylamide, and 70 parts of ethyl acetate; A method for preparing a double-base nano oil-water fracturing temporary plugging agent comprises the following preparation steps: Starch, acrylic acid, acrylamide, styrene and composite reinforcing materials are added to the solvent and stirred evenly. Dibenzoyl peroxide and N,N'-methylenebisacrylamide are added and stirred at 50°C for 30 minutes until the starch is gelatinized. The mixture is stirred and reacted at 73°C for 3 hours. The mixture is cooled to room temperature and washed with deionized water until a solid is precipitated. After the solid is dried, an oil-water fracturing temporary plugging agent is obtained.
[0041] The composite reinforced material is specifically prepared by the following steps: A1. Add 20 mL of 1-bromohexadecane and 11 mL of 2-(dimethylamino)ethyl methacrylate to 100 mL of ethanol, stir evenly, heat to 50°C, stir and react for 21 hours, then rotary evaporate, add acetone for recrystallization, take out, and wash with acetone three times to obtain a monomer; A2. 5 g of sodium montmorillonite was added to 50 mL of deionized water, stirred evenly, heated to 35 ° C, and stirred until no aggregates were observed, 0.5 g of monomer was added, stirred for 11 h, and the resulting product was washed with ethanol to remove water and excess monomers. The precipitate was filtered and dried in an oven at 50 ° C for 20 min to obtain modified montmorillonite; A3. Immerse 10 g of shell powder in 50 mL of 5.5% nitric acid solution for 45 min, remove it, wash it with deionized water until the washing solution is neutral, dry it in an oven at 70°C for 10 min, grind it in a grinder, and pass it through a 550-mesh sieve to obtain acidified shell powder; A4. Add 4.1g zirconium oxychloride octahydrate to 20mL deionized water, stir evenly, add 10mL of 28% ammonia water, 1g of glycine and 2g of potassium chloride, stir evenly, add 5.5g of acidified shell powder, stir at 85°C for 10min, place in a reactor, perform hydrothermal reaction at 180°C for 22h, cool to room temperature, filter, wash with deionized water until no chloride ions are detected in the supernatant with silver nitrate solution, and dry in an oven at 80°C for 3h to obtain shell powder loaded with nano zirconium dioxide; A5. 6 g of shell powder loaded with nano zirconium dioxide was added to 50 mL of N, N-dimethylformamide, stirred evenly, 2.5 g of stearic acid was added, stirred until the stearic acid was dissolved, stirred at 75 ° C for 21 h, filtered, washed with deionized water 3 times, and dried in an oven at 70 ° C for 20 min to obtain a composite; A6. Add 5.5 g of the composite and 1.5 g of modified montmorillonite to 50 mL of ethanol, stir evenly, stir at 55 ° C for 1.5 h, heat to 83 ° C, stir until the ethanol evaporates, take out the solid, wash the solid with deionized water three times, and dry it in an oven at 80 ° C for 10 min to obtain a composite reinforced material. Example
[0042] A double-base nano oil-water fracturing temporary plugging agent, comprising the following raw materials by weight: 12 parts of starch, 15 parts of acrylic acid, 22 parts of acrylamide, 12 parts of styrene, 6 parts of composite reinforcing material, 0.15 parts of dibenzoyl peroxide, 0.6 parts of N,N'-methylenebisacrylamide, and 80 parts of ethyl acetate; A method for preparing a double-base nano oil-water fracturing temporary plugging agent comprises the following preparation steps: Starch, acrylic acid, acrylamide, styrene and composite reinforcing materials are added to the solvent and stirred evenly. Dibenzoyl peroxide and N,N'-methylenebisacrylamide are added and stirred at 55°C for 35 minutes until the starch is gelatinized. The mixture is stirred and reacted at 75°C for 4 hours. The mixture is cooled to room temperature and washed with deionized water until a solid is precipitated. After the solid is dried, an oil-water fracturing temporary plugging agent is obtained.
[0043] The composite reinforced material is specifically prepared by the following steps: A1. Add 22 mL of 1-bromohexadecane and 12 mL of 2-(dimethylamino)ethyl methacrylate to 120 mL of ethanol, stir evenly, heat to 55°C, stir and react for 22 hours, then evaporate by rotary evaporation, add acetone for recrystallization, take out, and wash with acetone three times to obtain a monomer; A2. 6 g of sodium montmorillonite was added to 55 mL of deionized water, stirred evenly, heated to 35 ° C, and stirred until no aggregates were observed. 0.6 g of monomer was added and stirred for 12 h. The product was washed with ethanol to remove water and excess monomers. The precipitate was filtered and dried in an oven at 50 ° C for 20 min to obtain modified montmorillonite. A3. 12 g of shell powder was immersed in 55 mL of 6% nitric acid solution for 50 min, then taken out, washed with deionized water until the washing solution was neutral, dried in an oven at 70°C for 10 min, crushed in a grinder, and passed through a 600-mesh sieve to obtain acidified shell powder; A4. Add 4.3 g of zirconium oxychloride octahydrate to 22 mL of deionized water, stir evenly, add 12 mL of 30% ammonia water, 1.5 g of glycine and 3 g of potassium chloride, stir evenly, add 6 g of acidified shell powder, stir at 85 ° C for 10 min, place in a reactor, perform hydrothermal reaction at 185 ° C for 24 h, cool to room temperature, filter, wash with deionized water until the supernatant is undetectable with silver nitrate solution, and dry in an oven at 80 ° C for 3 h to obtain shell powder loaded with nano zirconium dioxide; A5. 7 g of shell powder loaded with nano zirconium dioxide was added to 55 mL of N, N-dimethylformamide, stirred evenly, 3 g of stearic acid was added, stirred until the stearic acid was dissolved, stirred at 80 ° C for 22 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 20 min to obtain a composite; A6. Add 6 g of the composite and 2 g of modified montmorillonite to 55 mL of ethanol, stir evenly, stir at 60 ° C for 2 h, heat to 85 ° C, stir until the ethanol evaporates, take out the solid, wash the solid with deionized water three times, and dry it in an oven at 80 ° C for 10 min to obtain a composite reinforced material.
[0044] Comparative Example 1 A double-base nano oil-water fracturing temporary plugging agent, comprising the following raw materials by weight: 12 parts of starch, 15 parts of acrylic acid, 22 parts of acrylamide, 12 parts of styrene, 6 parts of composite reinforcing material, 0.15 parts of dibenzoyl peroxide, 0.6 parts of N,N'-methylenebisacrylamide, and 80 parts of ethyl acetate; A method for preparing a double-base nano oil-water fracturing temporary plugging agent comprises the following preparation steps: Starch, acrylic acid, acrylamide, styrene and composite reinforcing materials are added to the solvent and stirred evenly. Dibenzoyl peroxide and N,N'-methylenebisacrylamide are added and stirred at 55°C for 35 minutes until the starch is gelatinized. The mixture is stirred and reacted at 75°C for 4 hours. The mixture is cooled to room temperature and washed with deionized water until a solid is precipitated. After the solid is dried, an oil-water fracturing temporary plugging agent is obtained.
[0045] The composite reinforced material is specifically prepared by the following steps: A1. Immerse 12 g of shell powder in 55 mL of 6% nitric acid solution for 50 min, remove it, wash it with deionized water until the washing solution is neutral, dry it in a 70°C oven for 10 min, grind it in a grinder, and pass it through a 600-mesh sieve to obtain acidified shell powder; A2. Add 4.3 g of zirconium oxychloride octahydrate to 22 mL of deionized water, stir evenly, add 12 mL of 30% ammonia water, 1.5 g of glycine and 3 g of potassium chloride, stir evenly, add 6 g of acidified shell powder, stir at 85 ° C for 10 min, place in a reactor, perform hydrothermal reaction at 185 ° C for 24 h, cool to room temperature, filter, wash with deionized water until the supernatant is undetectable with silver nitrate solution, and dry in an oven at 80 ° C for 3 h to obtain shell powder loaded with nano zirconium dioxide; A3. 7 g of shell powder loaded with nano zirconium dioxide was added to 55 mL of N, N-dimethylformamide, stirred evenly, 3 g of stearic acid was added, stirred until the stearic acid was dissolved, stirred at 80 ° C for 22 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 20 min to obtain a composite; A4. Add 6 g of the composite and 2 g of sodium montmorillonite to 55 mL of ethanol, stir evenly, stir at 60 ° C for 2 h, heat to 85 ° C, stir until the ethanol evaporates, take out the solid, wash the solid with deionized water three times, and dry it in an oven at 80 ° C for 10 min to obtain a composite reinforced material.
[0046] Comparative Example 2 A double-base nano oil-water fracturing temporary plugging agent, comprising the following raw materials by weight: 12 parts of starch, 15 parts of acrylic acid, 22 parts of acrylamide, 12 parts of styrene, 6 parts of composite reinforcing material, 0.15 parts of dibenzoyl peroxide, 0.6 parts of N,N'-methylenebisacrylamide, and 80 parts of ethyl acetate; A method for preparing a double-base nano oil-water fracturing temporary plugging agent comprises the following preparation steps: Starch, acrylic acid, acrylamide, styrene and composite reinforcing materials are added to the solvent and stirred evenly. Dibenzoyl peroxide and N,N'-methylenebisacrylamide are added and stirred at 55°C for 35 minutes until the starch is gelatinized. The mixture is stirred and reacted at 75°C for 4 hours. The mixture is cooled to room temperature and washed with deionized water until a solid is precipitated. After the solid is dried, an oil-water fracturing temporary plugging agent is obtained.
[0047] The composite reinforced material is specifically prepared by the following steps: A1. Add 22 mL of 1-bromohexadecane and 12 mL of 2-(dimethylamino)ethyl methacrylate to 120 mL of ethanol, stir evenly, heat to 55°C, stir and react for 22 hours, then evaporate by rotary evaporation, add acetone for recrystallization, take out, and wash with acetone three times to obtain a monomer; A2. 6 g of sodium montmorillonite was added to 55 mL of deionized water, stirred evenly, heated to 35 ° C, and stirred until no aggregates were observed. 0.6 g of monomer was added and stirred for 12 h. The product was washed with ethanol to remove water and excess monomers. The precipitate was filtered and dried in an oven at 50 ° C for 20 min to obtain modified montmorillonite. A3. Add 4.3 g of zirconium oxychloride octahydrate to 22 mL of deionized water, stir evenly, add 12 mL of 30% ammonia water, 1.5 g of glycine and 3 g of potassium chloride, stir evenly, add 6 g of shell powder, stir at 85 ° C for 10 min, place in a reactor, perform hydrothermal reaction at 185 ° C for 24 h, cool to room temperature, filter, wash with deionized water until the supernatant is undetectable with silver nitrate solution, and dry in an oven at 80 ° C for 3 h to obtain shell powder loaded with nano zirconium dioxide; A4. 7 g of shell powder loaded with nano zirconium dioxide was added to 55 mL of N, N-dimethylformamide, stirred evenly, 3 g of stearic acid was added, stirred until the stearic acid was dissolved, stirred at 80 ° C for 22 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 20 min to obtain a composite; A5. Add 6 g of the composite and 2 g of modified montmorillonite to 55 mL of ethanol, stir evenly, stir at 60 ° C for 2 h, heat to 85 ° C, stir until the ethanol evaporates, take out the solid, wash the solid with deionized water 3 times, and dry it in an oven at 80 ° C for 10 min to obtain a composite reinforced material.
[0048] Comparative Example 3 A double-base nano oil-water fracturing temporary plugging agent, comprising the following raw materials by weight: 12 parts of starch, 15 parts of acrylic acid, 22 parts of acrylamide, 12 parts of styrene, 6 parts of composite reinforcing material, 0.15 parts of dibenzoyl peroxide, 0.6 parts of N,N'-methylenebisacrylamide, and 80 parts of ethyl acetate; A method for preparing a double-base nano oil-water fracturing temporary plugging agent comprises the following preparation steps: Starch, acrylic acid, acrylamide, styrene and composite reinforcing materials are added to the solvent and stirred evenly. Dibenzoyl peroxide and N,N'-methylenebisacrylamide are added and stirred at 55°C for 35 minutes until the starch is gelatinized. The mixture is stirred and reacted at 75°C for 4 hours. The mixture is cooled to room temperature and washed with deionized water until a solid is precipitated. After the solid is dried, an oil-water fracturing temporary plugging agent is obtained.
[0049] The composite reinforced material is specifically prepared by the following steps: A1. Add 22 mL of 1-bromohexadecane and 12 mL of 2-(dimethylamino)ethyl methacrylate to 120 mL of ethanol, stir evenly, heat to 55°C, stir and react for 22 hours, then evaporate by rotary evaporation, add acetone for recrystallization, take out, and wash with acetone three times to obtain a monomer; A2. 6 g of sodium montmorillonite was added to 55 mL of deionized water, stirred evenly, heated to 35 ° C, and stirred until no aggregates were observed. 0.6 g of monomer was added and stirred for 12 h. The product was washed with ethanol to remove water and excess monomers. The precipitate was filtered and dried in an oven at 50 ° C for 20 min to obtain modified montmorillonite. A3. After washing the shell powder to remove the sludge, 12 g of the shell powder was immersed in 55 mL of a 6% nitric acid solution for 50 min, taken out, washed with deionized water until the washing solution was neutral, dried in an oven at 70°C for 10 min, crushed in a grinder, and passed through a 600-mesh sieve to obtain acidified shell powder; A4. 7 g of acidified shell powder was added to 55 mL of N,N-dimethylformamide, stirred evenly, 3 g of stearic acid was added, stirred until the stearic acid was dissolved, stirred and reacted at 80°C for 22 h, filtered, washed with deionized water three times, and dried in an oven at 70°C for 20 min to obtain a composite; A5. Add 6 g of the composite and 2 g of modified montmorillonite to 55 mL of ethanol, stir evenly, stir at 60 ° C for 2 h, heat to 85 ° C, stir until the ethanol evaporates, take out the solid, wash the solid with deionized water 3 times, and dry it in an oven at 80 ° C for 10 min to obtain a composite reinforced material.
[0050] Comparative Example 4 A double-base nano oil-water fracturing temporary plugging agent, comprising the following raw materials by weight: 12 parts of starch, 15 parts of acrylic acid, 22 parts of acrylamide, 12 parts of styrene, 6 parts of composite reinforcing material, 0.15 parts of dibenzoyl peroxide, 0.6 parts of N,N'-methylenebisacrylamide, and 80 parts of ethyl acetate; A method for preparing a double-base nano oil-water fracturing temporary plugging agent comprises the following preparation steps: Starch, acrylic acid, acrylamide, styrene and composite reinforcing materials are added to the solvent and stirred evenly. Dibenzoyl peroxide and N,N'-methylenebisacrylamide are added and stirred at 55°C for 35 minutes until the starch is gelatinized. The mixture is stirred and reacted at 75°C for 4 hours. The mixture is cooled to room temperature and washed with deionized water until a solid is precipitated. After the solid is dried, an oil-water fracturing temporary plugging agent is obtained.
[0051] The composite reinforced material is specifically prepared by the following steps: A1. Add 22 mL of 1-bromohexadecane and 12 mL of 2-(dimethylamino)ethyl methacrylate to 120 mL of ethanol, stir evenly, heat to 55°C, stir and react for 22 hours, then evaporate by rotary evaporation, add acetone for recrystallization, take out, and wash with acetone three times to obtain a monomer; A2. 6 g of sodium montmorillonite was added to 55 mL of deionized water, stirred evenly, heated to 35 ° C, and stirred until no aggregates were observed. 0.6 g of monomer was added and stirred for 12 h. The product was washed with ethanol to remove water and excess monomers. The precipitate was filtered and dried in an oven at 50 ° C for 20 min to obtain modified montmorillonite. A3. After washing the shell powder to remove the sludge, 12 g of the shell powder was immersed in 55 mL of a 6% nitric acid solution for 50 min, taken out, washed with deionized water until the washing solution was neutral, dried in an oven at 70°C for 10 min, crushed in a grinder, and passed through a 600-mesh sieve to obtain acidified shell powder; A4. Add 4.3 g of zirconium oxychloride octahydrate to 22 mL of deionized water, stir evenly, add 12 mL of 30% ammonia water, 1.5 g of glycine and 3 g of potassium chloride, stir evenly, add 6 g of acidified shell powder, stir at 85 ° C for 10 min, place in a reactor, perform hydrothermal reaction at 185 ° C for 24 h, cool to room temperature, filter, wash with deionized water until the supernatant is undetectable with silver nitrate solution, and dry in an oven at 80 ° C for 3 h to obtain shell powder loaded with nano zirconium dioxide; A5. Add 6 g of shell powder loaded with nano-zirconium dioxide and 2 g of modified montmorillonite to 55 mL of ethanol, stir evenly, stir at 60 ° C for 2 h, heat to 85 ° C, stir until the ethanol evaporates, take out the solid, wash the solid with deionized water 3 times, and dry it in an oven at 80 ° C for 10 min to obtain a composite reinforced material.
[0052] The performance of the temporary plugging agents for oil-water fracturing prepared in Examples 1-3 and Comparative Examples 1-4 was tested.
[0053] Dissolution time test: 5 g of the above-prepared oil-water fracturing temporary plugging agent was mixed with 100 g of fracturing fluid (84.6% clean water, 0.4% guar gum solution and 15% hydrochloric acid), added to the oil-water mixture of simulated formation water and kerosene, placed in a 60°C water bath, and the time for the oil-water fracturing temporary plugging agent to be completely dissolved was observed and recorded.
[0054] Degradation rate detection: 5 g (recorded as m1) of the above-prepared oil-water fracturing temporary plugging agent was added to 50 mL of deionized water, placed in an oven at 60°C for 24 h, filtered, dried, and weighed, recorded as m2. The degradation rate = (m1-m2) / m1×100%.
[0055] Salt resistance: The oil-water fracturing temporary plugging agent prepared above was added to formation water and 13.5 g / L sodium chloride solution respectively, and fully absorbed water and expanded at 20°C. After 4 hours, it was taken out and wiped dry with filter paper, and the shear strength was measured using a volume expansion particle strength shear instrument; Compressive strength test: The oil-water fracturing temporary plugging agent prepared above was extruded into a cylinder with a diameter of 6 mm and a height of 4 mm, and then the compressive strength was tested using a universal pressure tester; Permeability recovery rate test: After the artificial core (with known permeability K0) is passed through the fracturing fluid carrying the temporary plugging agent for oil-water fracturing, the permeability K1 of the artificial core is measured, and then the permeability K2 of the artificial core is measured after backwashing with salt water. Temporary plugging rate = (K0-K1) / K0×100%, and the core permeability recovery rate = K2 / K0×100%. As shown in Table 1 below.
[0056] Table 1 Performance test of temporary plugging agents for oil-water fracturing prepared in Examples 1-3 and Comparative Examples 1-4 project Dissolution time / h Shear strength / N Compressive strength / MPa Temporary blocking rate / % Core permeability recovery rate / % Degradation rate / % Example 1 20 216 116.6 99.6 99.4 99.8 Example 2 22 220 118.5 99.8 99.6 99.9 Example 3 21 214 115.9 99.5 99.2 99.7 Comparative Example 1 8 135 75.6 66.2 90.3 99.3 Comparative Example 2 10 146 80.1 75.6 92.3 99.5 Comparative Example 3 9 131 70.3 65.1 90.1 99.1 Comparative Example 4 19 155 81.2 61.3 92.3 99.2 It can be seen from the data in Table 1 that the temporary plugging agent for oil-water fracturing prepared in Examples 1-3 has good compressive strength and plugging rate, and has good degradability and core permeability recovery rate, and has a good temporary plugging and diversion effect. In Comparative Example 1, the composite reinforcing material prepared by replacing the modified montmorillonite with sodium-montmorillonite was added to the temporary plugging agent for oil-water fracturing, and its salt resistance and decreased, and the dissolution rate was fast, which proved that the monomer formed a hydrophobic network structure on the surface of the exfoliated sodium-montmorillonite, avoiding the water absorption and swelling rate of the temporary plugging agent for fracturing too fast, resulting in the temporary plugging agent for fracturing agglomeration and failure, affecting the plugging efficiency, and the monomer also has good salt resistance.
[0057] In Comparative Example 2, the composite reinforcing material prepared by replacing the acidified shell powder with shell powder was added to the oil-water fracturing temporary plugging agent, and its compressive strength and plugging efficiency decreased, indicating that the high specific surface area and pore structure of the acidified shell powder increased the contact area between the shell powder and the cracks, increased the density of the temporary plugging layer, and was conducive to the formation of nano zirconium dioxide on the surface and pores of the acidified shell powder.
[0058] In Comparative Example 3, the shell powder loaded with nano zirconium dioxide was replaced with a composite reinforcing material prepared by acidified shell powder and added to the oil-water fracturing temporary plugging agent. Its compressive strength and plugging efficiency decreased, and the dissolution rate was fast, indicating that the formation of nano zirconium dioxide on the surface and in the pores of the acidified shell powder reduces the water absorption rate of the acidified shell powder, avoids the shell powder absorbing water quickly, and affects the effective temporary plugging of the fracturing temporary plugging agent, and nano zirconium dioxide can effectively improve the compressive strength of the fracturing temporary plugging agent.
[0059] In Comparative Example 4, the composite material is replaced with a composite reinforcement material prepared by shell powder loaded with nano zirconium dioxide and added to the oil-water fracturing temporary plugging agent, which proves that stearic acid grafted on the surface of shell powder loaded with nano zirconium dioxide can be entangled with the long alkyl chains contained on the surface of modified montmorillonite to form hydrophobic channels, making it difficult for the water adsorbed into the interior of the oil-water fracturing temporary plugging agent to overflow, providing a large amount of water absorption and retention space for the oil-water fracturing temporary plugging agent, avoiding the dehydration of the colloidal particles becoming fragile and easy to break when the oil-water fracturing temporary plugging agent absorbs water and swells to form colloidal particles, thereby affecting the plugging effect.
[0060] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0061] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A dual-base nano oil-water fracturing temporary plugging agent, characterized in that: The method comprises the following raw materials in parts by weight: 10-12 parts of starch, 10-15 parts of acrylic acid, 20-22 parts of acrylamide, 10-12 parts of styrene, 5-6 parts of composite reinforcing material, 0.05-0.15 parts of initiator, 0.5-0.6 parts of cross-linking agent, and 60-80 parts of solvent; The composite reinforcement material is prepared by mixing shell powder loaded with nano zirconium dioxide, modified montmorillonite and stearic acid; The shell powder loaded with nano zirconium dioxide is prepared by subjecting shell powder to an acidification treatment, and then mixing it with zirconium oxychloride octahydrate, and then subjecting it to a hydrothermal reaction; The modified montmorillonite is prepared by reacting 1-bromohexadecane with 2-(dimethylamino)ethyl methacrylate and then mixing with montmorillonite.
2. The double-base nano oil-water fracturing temporary plugging agent according to claim 1, characterized in that: The composite reinforced material is specifically prepared by the following steps: A1. Add 1-bromohexadecane and 2-(dimethylamino)ethyl methacrylate to ethanol, stir evenly, heat to 45-55°C, stir and react for 20-22h, evaporate by rotary evaporation, add acetone for recrystallization, take out, wash and obtain a monomer; A2. The montmorillonite was added to deionized water, stirred evenly, the monomer was added, and stirring was continued for 10-12 hours. After washing with ethanol, the precipitate was filtered and dried to obtain the modified montmorillonite; A3. The shell powder was immersed in a nitric acid solution having a mass fraction of 5-6%, immersed for 40-50min, removed, washed, dried, placed in a grinder, and sieved through a 500-600 mesh screen to obtain acidified shell powder; A4. Add zirconium oxychloride octahydrate to deionized water, stir evenly, add 25-30% by mass of ammonia water, glycine and potassium chloride, stir evenly, add acidified shell powder, stir evenly, place in a reactor, perform hydrothermal reaction at 175-185°C for 20-24h, cool to room temperature, filter, wash and dry to obtain shell powder loaded with nano zirconium dioxide; A5. The shell powder loaded with nano zirconium dioxide is added to N, N-dimethylformamide, stirred evenly, stearic acid is added, stirred until the stearic acid is dissolved, stirred at 70-80 ° C for 20-22h, filtered, washed, and dried to obtain a composite; A6. Add the composite and modified montmorillonite to ethanol, stir evenly, stir at 50-60°C for 1-2h, heat to 80-85°C, stir until ethanol evaporates, take out the solid, wash and dry the solid to obtain a composite reinforced material.
3. A dual-base nano oil-water fracturing temporary plugging agent according to claim 2, characterized in that: In step A1, the volume ratio of 1-bromohexadecane, 2-(dimethylamino)ethyl methacrylate and ethanol is (18-22):(10-12):(80-120).
4. A dual-base nano oil-water fracturing temporary plugging agent according to claim 2, characterized in that: In step A2, the ratio of the amount of montmorillonite, deionized water and monomer is (4-6) g: (45-55) mL: (0.3-0.6) g.
5. The double-base nano oil-water fracturing temporary plugging agent according to claim 2, characterized in that: In step A3, the ratio of the shell powder to the nitric acid solution is (8-12) g: (45-55) mL.
6. The double-base nano oil-water fracturing temporary plugging agent according to claim 2, characterized in that: In step A4, the dosage ratio of zirconium oxychloride octahydrate, deionized water, ammonia water, glycine, potassium chloride and acidified shell powder is (3.9-4.3) g: (18-22) mL: (8-12) mL: (0.5-1.5) g: (1-3) g: (5-6) g.
7. The double-base nano oil-water fracturing temporary plugging agent according to claim 2, characterized in that: In step A5, the amount ratio of the shell powder loaded with nano zirconium dioxide, N,N-dimethylformamide and stearic acid is (5-7) g: (45-55) mL: (2-3) g.
8. The double-base nano oil-water fracturing temporary plugging agent according to claim 2, characterized in that: In step A6, the ratio of the composite, modified montmorillonite and ethanol is (5-6 g):(1-2) g:(45-55) mL.
9. The double-base nano oil-water fracturing temporary plugging agent according to claim 1, characterized in that: Prepared by the following steps: Add starch, acrylic acid, acrylamide, styrene and composite reinforcing material to the solvent, stir evenly, add initiator and cross-linking agent, stir at 45-55°C for 25-35 minutes, stir and react at 70-75°C for 2-4 hours, cool to room temperature, wash and precipitate solids, and dry the solids to obtain an oil-water fracturing temporary plugging agent.
Citation Information
Patent Citations
Preparation method of nano calcium carbonate-starch composite for drilling fluid
CN102134479A
Insertion plural gel granule and synthetic method thereof
CN103130954A
Biodegradable copolyester nanometer composite material and temporary plugging agent prepared from biodegradable copolyester nanometer composite material
CN104418999A
Fracturing temporary plugging agent and preparation method thereof
CN109054788A
Temporary plugging agent for drilling fluid and preparation method thereof, and water-based drilling fluid and use thereof
US10647902B1
Cited By
Intra-fracture diverting fracturing temporary plugging agent and preparation method thereof
CN121182475A
Temperature-resistant gel temporary plugging agent and preparation method thereof
CN121248847A